A pilot study on the efficacy of topical lotion containing anti-acne postbiotic in subjects with mild -to -moderate acne - Cui, Hongchang; Guo, Chaoqun; Wang, Qian; Feng, Congrui; Duan, Zhi (Frontiers in Medicine, 2022)
Acne can compromise facial esthetics and become a mental burden, especially when it occurs in puberty. Skincare cosmetics with anti-acne efficiency is more convenient than other treatment modalities, such as dietary supplements, in certain circumstances. The purpose of this study was to investigate the efficiency of an anti-acne lotion in alleviating acne. In our study, an anti-acne lotion containing ferment lysate produced by Lactiplantibacillus plantarum VHProbi® E15 were applied to subjects with mild -to -moderate acne over 4 weeks. The efficacy was evaluated based on instrumental measurements using Visia®-CR and CK-MPA® system. The anti-acne lotion exhibited favorable safety, meeting the stringent criteria for the detection of microbes, heavy metals, toxicity, and irritation. After 2 weeks of treatment, a statistically significant improvement in acne lesions was observed compared to baseline (P < 0.01), and this continued to the end of the study. After 4 weeks of treatment, the transepidermal water loss (P < 0.05) and sebum production (P < 0.05) were significantly decreased in subjects compared to baseline. In addition, the pore/area of interest (AOI) and stratum corneum hydration displayed slightly positive changes throughout treatment. Thus, we conclude that applying topical anti-acne lotion may be safe and confer effective benefits in people with mild -to -moderate acne and represents a promising therapeutic option for acne.